AN ASSESSMENT OF TOBACCO EXCISE ADMINISTRATION PRACTICES IN INDONESIA - Nauly, Yudhi Dharma (Politeknik Keuangan Negara STAN)
The global economic slowdown has unquestionably brought down the performance of the Indonesian economy. This, in turn, presented an extraordinary challenge to the Directorate General of Customs and Excise (DGCE) in collecting excise revenues. In the last few decades, tobacco has contributed the largest part of excise revenue. Accordingly, it is inevitable for the DGCE to implement best practices in administrating tobacco excise to optimize revenue collection, while at the same time, enhance public health. Conveniently, The World Health Organization (WHO) provides a series of extensive best practices in that particular field. This study assessed tobacco excise administration practices performed by the DGCE against best practices set by the WHO. This study revealed that, in general, the DGCE has performed well in several practices. However, there are some WHOâ€™s best practices which are unsuitable to be implemented in Indonesia. Unique fiscal, economic, political and social circumstances in Indonesia need to be taken into account in determining and establishing tobacco excise tax policy.Â